Need analysis: development of a teaching module for enhancing higher-order thinking skills of primary school students - Mat, Hamidah; Nusantara, Toto; Atmoko, Adi; Hanafi, Yusuf; Mustakim, Siti Salina (Institute of Advanced Engineering and Science, 2025)
This research identified a pressing need to create specialized teaching modules for electrical topics within the science curriculum that target students’ higher-order thinking skills (HOTS). Despite the recognized significance of HOTS in improving students’ educational achievements, science educators encounter obstacles when attempting to effectively teach these skills. To tackle this challenge, the study utilized a qualitative research methodology, conducting semi-structured interviews with six science teachers from diverse Malaysian schools. The primary objective was to pinpoint the necessity for developing instructional modules that enhance students’ HOTS in primary school science subjects. This study revealed four key themes arising from the needs assessment: the importance of HOTS knowledge, obstacles in teaching HOTS, effective teaching strategies, and the actual teaching of HOTS. This study underscores the critical need for enhanced professional development opportunities for teachers to effectively impart HOTS and stresses the importance of providing suitable teaching resources. By developing these tailored modules, students’ critical thinking and problem-solving skills can be nurtured, paving the way for their academic and professional success. Consequently, the study’s recommendations offer valuable insights for policymakers, educators, and researchers seeking to create impactful teaching modules that cater to students’ HOTS in primary school science subjects.